A new and presumably extinct species of Ptychochromoides (Teleostei: Perciformes: Cichlidae) from central Madagascar - Sparks, John S. (Zootaxa, 2004)
Ptychochromoides itasy, new species, is described from material collected from Lake Itasy and environs in the central highlands of Madagascar. The new species is distinguished from congeners by the presence of a pronounced occipital hump, regardless of size, sexual maturity, or sex, and also by a shorter predorsal length, more elongate terminal dorsal-fin spine, and shorter snout. Although reportedly once abundant in Lake Itasy, specimens referable to the new species have not been collected from the lake or surrounding region in several decades and the species is presumed to be extinct.